Clinical and MRI findings of brucellar spondylodiscitis - Bozgeyik, Zulkif; Ozdemir, Huseyin; Demirdag, Kutbettin; Ozden, Mehmet; Sonmugoz, Fitnet; Ozgocmen, Salih (Elsevier Ireland Ltd, 2008)
Objective: The aim of this retrospective study was to report the clinical features and MR imaging findings of patients with brucellar spondylodiscitis. Materials and methods: Twenty-two patients with spondylodiscitis, recruited among 152 patients with brucellosis referred from the Department of Infectious Diseases. Patients were diagnosed based on positive clinical findings, >= 1/160 titers of brucella agglutination tests and/or positive blood cultures. Magnetic resonance imaging (MRI) was performed to all of the patients with spondylodiscitis. Signal changes and enhancement of vertebral bodies, involvement of paravertebral soft tissues and epidural spaces, nerve root and cord compression and abscess formation were assessed. Results: All of the patients (n=22; 7 F, 15 M) had >= 1/160 titers of brucella agglutination test and blood culture was positive in 9. A great majority of the patients had involvement at only one vertebrae level (n=21, 95.5%), whereas one patient (4.5%) had multilevel involvement. In MRI, eight patients had soft tissue involvement and three had abscess formation. All cases had vertebral and discal enhancement. Additionally epidural extension was detected in four cases, posterior longitudinal ligament (PLL) elevation in five cases and root compression in two cases. Conclusion: Brucella is still a public health problem in endemic areas. MRI is a highly sensitive and non-invasive imaging technique which should be first choice of imaging in the early diagnosis of spondylodiscitis. (c) 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: spine; brucella; spondylodiscitis; MRI